PTH-149 A One Stop Iron Deficiency Anaemia Clinic: A Review of Its Efficacy. (17th August 2016) - Lau, MS; Schembri, J; Sanders, DS; Hebden, JM
Abstract : Introduction: Iron deficiency anaemia (IDA) accounts for 4–13% of referrals to gastroenterology. A single consultant led one stop IDA clinic was set up to streamline all required tests (upper and lower gastrointestinal investigations, coeliac serology, intrinsic factor antibodies, immunoglobulins, urinalysis and ultrasound, or CT if appropriate) at the first clinic in order to reach a diagnosis quicker and reduce unnecessary follow ups. We aimed to evaluate the discharge rate after the first clinic visit compared to patients with IDA attending general gastroenterology clinics, and assess the patients' compliance of haemoglobin (Hb) monitoring by general practitioners (GP) and response to iron post discharge to primary care. Methods: We prospectively reviewed all cases referred with iron deficiency (IDA and isolated hypoferritanaemia) attending the clinic from 2013–14. The discharge rate after the first visit was analysed. We assessed the discharged patients' response to iron at 3 or 6 months, defined by normalisation of Hb, excluding those with cancer. We reviewed their compliance with Hb monitoring at 3, 6, 9 and 12 months as advised by the consultant in clinic and also via letters to the GPs and patients, and compared it to that of patients who were followed up in clinic. Results: A total of 214 iron deficient patients attended the clinic. The discharge rate was 90.2% (193/214) versus 26% for IDA patients attending general gastroenterology clinics (80% consultant led) in our previously published data in 2014. We excluded 24 patients with cancer, and 19 who did not have their Hb checked at 3 or 6 months, leaving 150 discharged patients for analysis. 51.3% (77/150) responded to iron therapy at 3 or 6 months. Of those, 68.8% (33/48) had a sustained response at 12 months after excluding 29 patients who did not have their Hb checked at 12 months. The compliance rate for Hb monitoring by the GP at 3, 6, 9 and 12 months in the discharged group was 24.9% (42/169), versus 9.5% (2/21) in the follow up group. Conclusion: This one stop IDA clinic had a significantly higher discharge rate compared to general gastroenterology clinics for IDA patients. Half of the discharged patients had an initial response to iron, where two thirds of them had a sustained response at 12 months. It is unclear whether this was due to poor adherence to iron therapy or missed pathologies, however all patients underwent a comprehensive range of investigations. The compliance with Hb monitoring was low in both the discharge and follow up groups, suggesting that compliance was not necessarily related to whether the patient was followed up or discharged. Further emphasis is needed to relay the importance of Hb monitoring to both patients and GPs, in order to identify those who may require further investigations. Disclosure of Interest: None Declared